Respuesta :

Answer:

x = 12 , y = -3

Step-by-step explanation:

Solve the following system:

{2 x + 7 y = 3 | (equation 1)

x = -4 y | (equation 2)

Express the system in standard form:

{2 x + 7 y = 3 | (equation 1)

x + 4 y = 0 | (equation 2)

Subtract 1/2 × (equation 1) from equation 2:

{2 x + 7 y = 3 | (equation 1)

0 x+y/2 = -3/2 | (equation 2)

Multiply equation 2 by 2:

{2 x + 7 y = 3 | (equation 1)

0 x+y = -3 | (equation 2)

Subtract 7 × (equation 2) from equation 1:

{2 x+0 y = 24 | (equation 1)

0 x+y = -3 | (equation 2)

Divide equation 1 by 2:

{x+0 y = 12 | (equation 1)

0 x+y = -3 | (equation 2)

Collect results:

Answer: {x = 12 , y = -3

Answer:

x = 12 y = -3

Step-by-step explanation: